Half-dose fulvestrant plus anastrozole as a first-line treatment for hormone receptor-positive metastatic breast cancer: a cost-effectiveness analysis. Issue 8 (30th August 2020) - Huang, Xiaoting; Weng, Xiuhua; Lin, Shen; Liu, Yiwei; Luo, Shaohong; Wang, Hang; Ming, Wai-kit; Huang, Pinfang
Abstract : Objective: The S0226 trial demonstrated that the combination of half-dose fulvestrant (FUL) and anastrozole (ANA) (F&A) caused a significant improvement in overall survival (OS) versus ANA monotherapy for first-line treatment of postmenopausal women with hormone receptor-positive metastatic breast cancer (PMW-MBC (HR+)). The objective of this study was to evaluate the cost-effectiveness of F&A in the first-line treatment for PMW-MBC (HR+) in China. Design: We constructed a Markov model over a life-time horizon. The clinical outcomes and utility data were obtained from published literature. Cost data were obtained from official Chinese websites. Sensitivity analyses were performed to test result uncertainty. Setting: Chinese healthcare system perspective. Population: A hypothetical cohort of adult patients presenting with PMW-MBC (HR+). Interventions: F&A compared with full-dose FUL and ANAmonotherapy. Main outcome measures: The main outcome of this study was the incremental cost-effectiveness ratio (ICER) and quality-adjusted life-years (QALY). Results: ANA was estimated to have the lowest cost and minimum life-years. The ICER of F&A versus ANA was US15 665.891/QALY with incremental cost and QALY of US12 401.120 and 0.792, respectively, which was less than the willingness-to-pay of US29 383/QALY. Compared with F&A, FUL yielded a higher cost and a shorter lifetime; hence, it was identified as a dominated strategy. The univariate sensitivity analysis indicated the price of FUL was the most influential factor in our study. The probability that F&A was cost-effective at a threshold of US29 383/QALY in China was 86.5%. Conclusion: F&A is a cost-effective alternative to FUL and ANA monotherapy for the first-line treatment of PMW-MBC (HR+) in China. F&A is a promising first-line treatment for PMW-MBC (HR+), and more research is needed to evaluate the economy of using F&A in other countries.